Chitosan-Cinnamon Oil Coating Maintains Quality and Extends Shelf Life of Ready-to-Use Pomegranate Arils under Low-Temperature Storage. (9th July 2022) - Singla, Mohit; Pareek, Sunil; Kumar, Nishant; Sagar, Narashans Alok; Fawole, Olaniyi Amos
Abstract : Different formulations of chitosan (1%, 2%, or 3%) with the incorporation of cinnamon oil (0.25% or 0.50%) were prepared for the preservation of pomegranate aril cv. Bhagwa. Six combinations of chitosan-cinnamon oil formulations along with one control (untreated) were applied to the freshly extracted arils using the dipping application method. All treatments were found to be effective in enhancing the shelf life, improving the postharvest characteristics, and reducing microbial populations on pomegranate arils during a 15-day storage period at 4 ± 1°C. The treated pomegranate arils exhibited excellent resistance to microbial decay, moisture loss, respiration rate, preservation of phenolics, flavonoids, and antioxidants activity, among other characteristics. Chitosan 2% + cinnamon oil 0.25% edible coating has a high potential to enhance the storage life and biochemical properties and reduce the microbial population of arils. This treatment recorded a higher total phenolic content (18%) and antioxidant activity (16%) than the control sample, respectively, at the end of storage. In addition, the treatment also helped to decrease the microbial activity by 45% compared to the control sample. The present investigation proposed an alternative method to prolong the shelf life of pomegranate arils during the 15 days of storage.